KURIKULUM KESENIAN PASCA GEMPA SD/MI DI DAERAH ISTIMEWA YOGYAKARTA - Rumi Wiharsih (FBS UNY, 2006)
The curriculum applied in the earthquake areas is that which isadjusted to the present situation and condition. Physically and psychologically,the human resources will be different from the normal situation before theearthquake happened. The curriculum that is specially designed to recover thepost-earthquake condition is called post-earthquake or emergency curriculum.This curriculum will be implemented temporarily to support the main curriculumthat has been applied in the previous normal situation and condition. Thecurriculum is designed using post-earthquake psychological-social approach. Theaims are formulated to create fun teaching-learning situation in class and toeradicate the students’ trauma caused by the earthquake.Key words: curriculum, earthquake victims and psycho-social approach